Lower Gastrointestinal Hemorrhage Caused by Superior Rectal Artery Pseudoaneurysm. Issue 6 (16th June 2020) - Nguyen, Christopher; Baliss, Michelle; Tayyem, Obada; Merwat, Shehzad
ABSTRACT: Acute lower gastrointestinal (GI) bleeding is self-limiting and managed conservatively. Ongoing bleeding from a lower GI source and hemodynamic instability can create difficult diagnostic and therapeutic dilemmas. The severity of bleeding can necessitate emergent diagnostic and therapeutic interventions. Diverticulosis and angiodysplasias are the most common causes of massive lower GI hemorrhage. Other etiologies that can lead to life-threatening hemorrhage are important to recognize. We present a rare case of massive lower GI hemorrhage attributable to a superior rectal artery pseudoaneurysm. The absence of a preceding traumatic or iatrogenic cause distinguishes this case from other reports in the literature.